The timing of the first primary tooth eruption and the symptoms of teething in children in Latakia (Cohort study) - Raslan, Nabih; Ahmad, Noor (Latakia University Journal -Medical Sciences Series, 2019)
Aim: To determine the timing of eruption the first primary tooth in the children of Lattakia city and to identify the most common signs and symptoms of teething. Materials and Methods: A prospective descriptive study in which the sample was collected from the health centers of Lattakia city, 300 children from the centers were examined. They were followed through periodic examination or contact with the parents, and the date of the first tooth eruption was written in the form for each child. Examination was conducted by direct seeing and palpation using rubber gloves and under the light of the dentalchair. Results: The average time for the emergence of the first primary tooth in the children was 8.11 months with a standard deviation of 1.991.The mandibular central incisor was the first of the emerged teeth, and the sequence of eruption of the primary incisors was:The mandibular central incisor, the maxillary central incisor, the maxillary Lateral incisor, and the mandibular lateral incisor, Teething was accompanied by drooling and fever by a percentage of 62% and 35.7%.respectivily. CONCLUSIONS: There was no delay in the timing of the eruption of the first primary tooth in the children of Lattakia, and that drooling and fever are the most common clinical manifestations of teething. ا لهدف: تحديد زمن بزوغ أول سن مؤقتة عند أطفال مدينة اللاذقية وتمييز علامات وأعراض التسنين الأكثر شيوعاً، وعلاقتها ببزوغ أكثر من سن معاً. المواد والطرق: دراسة وصفية مستقبلية تم فيها جمع العينة من المراكز الصحية لمحافظة اللاذقية، تم فحص 300طفلاً من الأطفال المراجعين للمراكز الصحية، وتمت متابعتهم من خلال الفحص الدوري أو التواصل مع الأهل وتسجيل موعد بزوغ أول سن في الاستمارة الخاصة بكل طفل، أجري الفحص بالرؤية المباشرة والجس باستخدام الكفوف المطاطية وتحت ضوء كرسي الأسنان. النتائج: كان متوسط زمن بزوغ أول سن مؤقتة عند الأطفال هو 8.11 شهراً بانحراف معياري قدره 1.99، وكانت الثنية السفلية المؤقتة أولى الأسنان البازغة، وسجل تسلسل بزوغ القواطع المؤقتة كالتالي: ثنايا سفلية –ثنايا علوية –رباعيات علوية - رباعيات سفلية، تم تسجيل ترافق التسنين مع الإلعاب والحرارة بنسبة مئوية قدرها 62%و35.7% على الترتيب. الاستنتاجات: لم يكن هناك تأخر في توقيت بزوغ أول سن مؤقتة لدى أطفال مدينة اللاذقية، وكانت المظاهر السريرية الأكثر انتشاراً للتسنين هي الإلعاب والحرارة.